Reliability estimation by usage rate method varying the quantity of warranty data censored - Neto, Eugenio Zappa [UNESP]; de Souza, Gilberto Fransciso Martha; Silva, Messias Borges [UNESP] (Research Publishing Services, 2020)
With an ever faster, more competitive market, and more demanding consumers who cannot tolerate product failures that are backed by consumer protection and protection laws, companies need to strive to improve the reliability of their products, that means perform its the function without fail in a certain desirable time, under the most diverse real conditions. However, even with the application of technologies in product development and manufacturing, failures still occur. Although the warranty data that companies have of their products is a valuable source of information that give the real conditions that the products are performed, its using for the reliability product estimation is not direct applicable because it is incomplete and require appropriates methods for its use. This work aims to apply the method of censoring by usage rate varying the quantity of field data that enables the use of warranty data in more accurate reliability analyzes so that companies can improve their products. Through a literature review and the use of warranty data, the feasibility of applying the usage rate censored method was verified. With statistical proof, the proposed guarantee data modeling method reached the results of the adopted reference study. It is concluded that the amount of censored data influences the lifetime result, and that in this case study, values closer to the reference value were obtained for quantities of censored data between 60 to 90% of the total population. Therefore, its application can contribute to the development of quality, increase customer satisfaction and gain competitive advantage for the companies to apply it.
Keywords: Automotive; Censored Data; Reliability Engineering; Usage Rate Method; Warranty data